Penyusunan Menu Makanan Sehat untuk Balita Stunting di Kelurahan Bandarharjo Kota Semarang - Mulyanti, Lia; Lutfitasari, Ariyani; Nor Fatima, Puji (Jurnal SOLMA, 2023)
Background: Stunting is a condition where babies or children under five years old experience stunting and are malnourished from the time they are still in the womb until they are born. Stunting will begin to appear when the child is two years old. Prolonged problems with malnutrition can cause height growth problems in children, meaning that children become shorter (stunted) than children of the same age. The purpose of the community service activity is to provide knowledge about preparing healthy food menus to mothers who have stunted toddlers. Method: This community service was carried out by conducting outreach and practicing healthy food menu preparation in the Bandarharjo sub-district, Semarang City with a total of 20 participants. Community service participants are mothers who have stunted toddlers. Result: The results of community service regarding preparing healthy food menus for toddlers are very good. Participants were enthusiastic about the material presented. Conclusions: Awareness of the importance of paying attention to fulfilling nutrition for toddlers who experience stunting.